Characterization of skn-1/wdr-23 phenotypes in Caenorhabditis elegans; pleiotrophy, aging, glutathione, and interactions with other longevity pathways. (July 2015) - Tang, Lanlan; Choe, Keith P.
Highlights: Multiple phenotypes of wdr-23 are completely dependent on skn-1 . SKN-1 control of stress resistance and longevity can be decoupled from growth and reproduction. SKN-1 delays degenerative tissue changes during aging. SKN-1 promotes total glutathione as a mechanism of longevity when activated by wdr-23 loss. Other mechanisms are used during reduced insulin/IGF-like signaling and dietary restriction. Abstract: The SKN-1/Nrf transcription factors are master regulators of oxidative stress responses and are emerging as important determinants of longevity. We previously identified a protein named WDR-23 as a direct repressor of SKN-1 in C. elegans . Loss of wdr-23 influences stress resistance, longevity, development, and reproduction, but it is unknown if WDR-23 influences development and reproduction solely through SKN-1 and the mechanisms by which SKN-1 promotes stress resistance and longevity are poorly defined. Here, we characterize phenotypes of wdr-23 and skn-1 manipulation and explore the role of glutathione. We provide evidence that diverse wdr-23 phenotypes are dependent on SKN-1, that beneficial and detrimental phenotypes of wdr-23 and skn-1 can be partially decoupled, and that SKN-1 activation delays degenerative tissue changes during aging. We also show that total glutathione levels are substantially elevated when the wdr-23/skn-1 pathway is activated and that skn-1 is required for preserving this cellular antioxidant during stress and aging. Alternatively, total glutathione was not elevated in worms with reduced insulin/IGF-1-like signaling or dietary restriction suggesting that SKN-1 ensures longevity via different mechanisms under these conditions. Lastly, genetic interaction data revise our understanding of which skn-1 variants are required for longevity during dietary restriction.